Modern methods and forms of interference in the internal affairs of countries - Benchabane, Mohamed Salah; Bencheikh el fegoun, Soumia (Journal of Human Sciences, 2022)
The subject of the article, is conclusions about the strange developments that the world has witnessed in relation to interference in the internal affairs of states, and a dilution of the first concept that was developed with the end of World War II and the General Assembly’s recommendation No.: 2131 dated: December 21, 1965 entitled to declare non-interference in The internal affairs of states and the protection of their independence and sovereignty by the prohibition of all forms of interference,And Article Two of the Charter of the United Nations and other international covenants.Why this shift, what is its legal and political background, what are the declared and undeclared reasons for interfering in the internal affairs of states, what are the new and innovative methods for carrying out intervention in the internal affairs of states, and can solutions be found to limit from interfering in the internal affairs of states?